Heterocellular cadherin connections: coordinating adhesive cues in homeostasis and cancer [version 1; peer review: 2 approved] - Fontenete, Silvia; Peña Jimenez, Daniel; Pérez Moreno, Mirna (My University, 2017)
This short insight covers some of the recent topics relevant to the field of cadherin¿catenin adhesion in mediating connections between different cell types, so-called heterotypic or heterocellular connections, in both homeostasis and cancer. These scientific discoveries are increasing our understanding of how multiple cells residing in complex tissues can be instructed by cadherin adhesion receptors to regulate tissue architecture and function and how these cadherin-mediated heterocellular connections spur tumor growth and the acquisition of malignant characteristics in tumor cells. Overall, the findings that have emerged over the past few years are elucidating the complexity of the functional roles of the cadherin¿catenin complexes. Future exciting research lies ahead in order to understand the physical basis of these heterotypic interactions and their influence on the behavior of heterogeneous cellular populations as well as their roles in mediating phenotypic and genetic changes as cells evolve through complex environments during morphogenesis and cancer. Keywords Cadherin catenin, heterocellular adhesion, heterotypic adhesion, cancer, Cadherin adhesion